Free semigroups in wreath powers of transformation semigroups - Oliynyk, A. (Algebra and Discrete Mathematics, 2010)
It is established a criterion when the infinite wreath power of a finite transformation semigroup contains a free subsemigroup. It is shown that the infinite wreath power of a transformation semigroup either contains no free non-commutative subsemigroups or most of its finitely generated subsemigroups are free.